Pengujian Fungsionalitas dan Keandalan Sistem Laundry Berbasis Web - Amar Naufal; Abdul Habib Hasibuan (Journal of Information Systems and Business Technology, 2025)
This study aims to test the quality of a web-based clothing system from the aspects of functionality and reliability. As the need for efficient and easily accessible clothing services increases, the development of a web-based system becomes a relevant solution. The system was tested using the Dark Box Testing method to evaluate the performance of each feature based on real-world usage scenarios. The development approach used was Rapid Application Development (RAD), which allows rapid iteration through the creation and refinement of prototypes based on user feedback. Testing focused on key features such as login, customer management, clothing transactions, and revenue reporting. The test results showed that most features ran as expected and supported clothing operations effectively, although one case failed in recording transactions. These findings provide an important picture of the advantages of the system and the range that needs improvement. This study is expected to be a reference in the development of similar service systems in the future.